The Effect of Medicaid Expansions on the Health Insurance Coverage of Pregnant Women: An Analysis Using Deliveries - Dhaval M. Dave; Sandra L. Decker; Robert Kaestner; Kosali Ilayperuma Simon (SAGE Publishing, 2010)
Using data from the National Hospital Discharge Survey, this paper analyzes the effect of Medicaid eligibility expansions from 1985 to 1996 on the health insurance coverage of women giving birth. We find that the eligibility expansions reduced the proportion of pregnant women who were uninsured by approximately 10%, although the magnitude of this decrease is sensitive to specification. The decrease in the proportion of uninsured pregnant women came at the expense of a substantial reduction in private insurance coverage (crowd-out) of at least 55%. Substantial crowd-out and the relatively small change in the proportion uninsured suggest that Medicaid eligibility expansions may have had small effects on infant and maternal health.